2011
DOI: 10.1038/cgt.2011.53
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic adenovirus armed with human papillomavirus E2 gene in combination with radiation demonstrates synergistic enhancements of antitumor efficacy

Abstract: High-risk human papillomavirus (hr-HPV) E6 and E7 oncogenes are associated with resistance to radiotherapy in cervical cancer. Efforts have been taken to employ HPV E2, a crucial negative transcriptional modulator of HPV E6 and E7 oncogenes, and also an apoptosis-inducing agent, for therapeutic intervention. Despite being conceptually attractive, the potency and feasibility of current hr-HPV E2-based therapies remain limited. Here, we designed a novel recombinant adenovirus, named M5, with a 27-bp deletion in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 34 publications
(41 reference statements)
0
19
0
Order By: Relevance
“…All 11 records are experimental study designs involved in testing the HPV–16 E2 protein in vitro. There was only one in vivo study where the combination of radiation treatment and fusion protein E2 was carried out in mice [ 20 ]. A total of four studies were conducted in the United Kingdom (UK) [ 22 , 23 , 24 , 25 ] and China [ 19 , 20 , 21 , 26 ], respectively, two in India [ 27 , 28 ], and another one in Mexico [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All 11 records are experimental study designs involved in testing the HPV–16 E2 protein in vitro. There was only one in vivo study where the combination of radiation treatment and fusion protein E2 was carried out in mice [ 20 ]. A total of four studies were conducted in the United Kingdom (UK) [ 22 , 23 , 24 , 25 ] and China [ 19 , 20 , 21 , 26 ], respectively, two in India [ 27 , 28 ], and another one in Mexico [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to controlling transcription and viral DNA replication, E2 proteins physically interacted with cellular proteins to have an impact on the biology of the host cell [ 16 ]. The involvement of the E2 protein in apoptosis occurred via the p53-dependent and p53-independent pathway, receptor-signaling pathway, and mitochondria-dependent pathway [ 16 , 17 , 18 , 19 , 20 , 21 ]. Published studies showed that E2 induces apoptosis indirectly, via its effects on the expression of E6 and E7, and directly, via its interaction with p53 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the oncolytic virotherapy approach, the use of five different Ads, i.e., rAd-M5, rAd-M6, rAd-53 [112], rAd-VEGFI-251, and rAd-H101 [113], demonstrated significant anti-tumour effects both in vitro and in vivo and led to increased apoptosis of cancer cells. rAd-M5 expressed the HPV E2 gene, which negatively regulated E6 and E7 expression and led to growth suspension and increased apoptosis [110], while rAd-M6 employing antisense HPV16 E6/E7 DNA inhibited the expression of E6 and E7 and induced apoptosis in vitro and in vivo [111]. In another study, Xiao et al used an oncolytic adenovirus expressing the VEGF inhibitor VEGI-251 and demonstrated the induction of apoptosis and the inhibition of neovascularisation [114], while Wang et al, employing rAd-p53 carrying the promoter of early growth response (Egr-1), and the anti-apoptotic TNF-related apoptosis-inducing ligand (TRAIL) gene showed increased radiotherapyinduced apoptosis in cell lines and tumour size reduction in xenograft mice [112].…”
Section: Lentivirusesmentioning
confidence: 99%
“…Wang et al developed a tumor-specific replication-competent oncolytic rAd, M5, expressing the HPV16 E2 gene. This combination of the oncolytic ability with gene silencing showed potent antitumoral efficacy in vitro and in vivo, due to viral replication, apoptosis and growth suppression [96]. Another system based on the insertion of a secreted isoform of VEGF inhibitor (VEGI-251) into an oncolytic adenoviral system with E1B 55 kDa gene deletion (ZD55) was described [97].…”
Section: Oncolytic Virotherapymentioning
confidence: 99%
“…The synergistic effect of oncolytic virotherapy combined with RT has also been demonstrated in other studies. Wang et al showed that the combined treatment with radiation and M5 Ad expressing HPV16 E2 gene [96] or M6 Ad with antisense HPV16 E6 E7 DNA [99] inhibits the expression of these oncogenes and induced apoptosis in cervical cancer cells both in vitro and in vivo. M6 Ad could be improved by the introduction of the HPV18 E6 E7 DNA antisense, thus also achieving an antitumor effect in HPV18-related cancer cells.…”
Section: Oncolytic Virotherapymentioning
confidence: 99%